Cutaneous filarioid nematodes of dogs in the United States: Are they emerging, neglected, or underdiagnosed parasites? - Gruntmeir, Jeff; Kelly, Maureen; Ramos, Rafael Antonio Nascimento; Verocai, Guilherme Gomes (Frontiers in Veterinary Science, 2023)
Filarioid nematodes, which are vector-borne parasites of cosmopolitan distribution, of dogs are medically important. They are represented by species in which microfilariae were found to be circulating in the bloodstream (e.g., Dirofilaria sp., Acanthocheilonema sp., and Brugia sp.) or skin-dwelling (e.g., Cercopithifilaria sp. and Onchocerca sp.). Those species whose microfilariae are detected in blood have been extensively studied, especially Dirofilaria immitis, due to their clinical importance. In recent decades, there has been an increased interest by the scientific community in filarioid nematodes whose microfilariae are detected in the skin because of the zoonotic aspect of Onchocerca lupi. In the United States (US), although D. immitis has been considered the main filarioid infecting dogs, the intense animal movement and global canine filarioid diversity may indicate that the likely presence of cutaneous filarioid nematodes is more common than previously expected. Hence, a question remains: Are these canine filarioid nematodes emerging, neglected, or simply underdiagnosed in the US? In this review, we provide an overview of pertinent information that briefly summarizes the biology of the different canine filarioid nematode species, clinical signs associated with infections, and currently available diagnostic tools using molecular and microscopy-based methods and highlight knowledge gaps where research and surveillance efforts remain necessary. The data herein presented serve as an alert to the scientific community about the importance of filarioid nematodes infecting dogs other than D. immitis. Additionally, the zoonotic potential of several filarioid species reinforces the necessity of a proper diagnosis and the need for broader surveillance to understand their diversity and distribution, to highlight the potential introduction of certain species, and mitigate their establishment in the country and new animal and human cases.